2020
DOI: 10.1186/s12913-020-05496-9
|View full text |Cite
|
Sign up to set email alerts
|

Measuring productivity of healthcare services under environmental constraints: evidence from China

Abstract: Background: Despite the growing literature on the efficiency and productivity of the Chinese healthcare system, less attention has been given to examining the undesirable outputs linked to healthcare services, including environmental pollution. Taking the atmospheric environmental pollution resulting from the incineration of medical waste as an undesirable output of the healthcare system, this study analyzed the growth and decomposition of Total Factor Productivity (TFP) of healthcare services across 31 Chines… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 48 publications
1
7
1
Order By: Relevance
“…The operation level of medical and health institutions is not high, and it is necessary to introduce talents to improve their management level. Thirdly, the total factor productivity of medical and health institutions in China decreased by 3.5% annually from 2012 to 2017, mainly due to insufficient technological progress, which is slightly different from the research conclusion of Yu et al and Chen et al 32,33 Effech and Techch were 0.998 and 0.967, respectively, with an average annual decrease of 1.2% and 3.3%. Meanwhile, none of the provinces with falling TFP has achieved technological progress.…”
Section: Summary and Discussioncontrasting
confidence: 57%
“…The operation level of medical and health institutions is not high, and it is necessary to introduce talents to improve their management level. Thirdly, the total factor productivity of medical and health institutions in China decreased by 3.5% annually from 2012 to 2017, mainly due to insufficient technological progress, which is slightly different from the research conclusion of Yu et al and Chen et al 32,33 Effech and Techch were 0.998 and 0.967, respectively, with an average annual decrease of 1.2% and 3.3%. Meanwhile, none of the provinces with falling TFP has achieved technological progress.…”
Section: Summary and Discussioncontrasting
confidence: 57%
“…Mankelow, found that the teaching staff used a three-pronged approach to observe the students' development and use thought leadership to ensure that the students were able to relate their inner world to the reality of their thoughts [ 7 ]. Yu, et al took the initiative to look for problems in the course of teaching activities and raised them to the teaching staff to ensure that the teachers were able to provide answers to the students and understand the basic behavioral orientation of the students at the moment [ 8 ]. Samoilenko and Osei-Bryson, found that it was the only way to ensure that the school's party organization could play its true role in equipping students with the appropriate ideals and beliefs to meet the needs of teaching and learning activities, using theoretical learning, cultural activities, professional teaching and interaction to ensure that students have the correct world view, outlook on life and values [ 9 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Yu et al (2020) evaluated the efficiency of healthcare systems in 31 Chinese provinces during the period 2005-2016 based on changes in total factor productivity (TFP). The results confirmed that significant changes occurred in TFP in the period 2009-2016.…”
Section: Operational Efficiency Of Isolation Hospitalsmentioning
confidence: 99%